Cardiac troponin T as a marker of myocardial damage caused by antineoplastic drugs in rabbits - Adamcová, M; Gersl, V; Hrdina, R; Melka, M; Mazurová, Y; Vávrová, J; Palicka, V; Kokstein, Z (Journal of cancer research and clinical oncology, 1999)
Anthracycline derivatives are among the most effective antineoplastic drugs but their therapeutic use is limited by their adverse effects. The cardiac side-effects of antineoplastic drugs were investigated in rabbits in vivo from the viewpoint of release of cardiac troponin T (cTnT) measured by Elecsys Troponin T STAT immunoassay (Boehringer Mannheim, Germany). No increase in cTnT was found following administration of a single dose of daunorubicin (3 mg/kg i.v., n = 4). During development of daunorubicin-induced cardiomyopathy (daunorubicin 3 mg/kg i.v., once a week; maximum nine administrations, n = 7), the levels of cTnT were within the physiological range (i.e. cTnT <0.1 microg/l) at the beginning of the experiment and before and after the 5th administration, but the pathological values of cTnT after the 8th administration in 43% animals (0.22+/-0.08 microg/l) correlated with their premature death. In the control group, the levels of cTnT were always lower than 0.1 microg/l during the experiment. Following administration of a new antineoplastic drug - Oracin [6-[2-(2-hydroxyethyl) aminoethyl]-5,11-dioxo-5,6-dihydro-11H-indeno [1,2-c]-isoquinoline hydrochloride, 10 mg/kg i.v., once weekly, ten administrations, n = 7], there was no increase in cTnT levels. These findings correlated with the PEP: LVET index, histological examination and no animal succumbing to premature death. It is possible to conclude that cTnT is a useful marker for the prediction of experimentally induced anthracycline cardiomyopathy and for the evaluation of cardiotoxic (and, possibly, cardioprotective) effects of new drugs in rabbits.
Keywords: Infusions, Intravenous; Male; biologické markery; intravenózní infuze; ethanolaminy; protinádorové látky; protinádorová antibiotika; Biomarkers; Cardiomyopathies; Drug Administration Schedule; Ethanolamines; Troponin T; Myocardium; daunomycin; mužské pohlaví; kardiomyopatie; troponin T; králíci; Animals; Daunorubicin; isochinoliny; zvířata; Antibiotics, Antineoplastic; Rabbits; Isoquinolines; rozvrh dávkování léků; myokard; Antineoplastic Agents